The Response of Sugar Beet (Beta vulgaris L.) Genotypes at Different Ploidy Levels to Salt (NaCl) Stress - Murat Aycan; Emine Gulden Erkilic; Yasin Ozgen; Irem Poyraz; Mustafa Yildiz (International Journal of Plant Biology, 2023)
Sugar beet (Beta vulgaris L.) is cultivated in temperate climates worldwide to produce sugar. The production of sugar beet and other plants is in danger due to the world’s increasingly salinized soils. Although different sugar beet genotypes exist at various ploidy levels, most of them are diploid (2X) with 18 chromosomes. The majority of polyploid plants have different variations, morphologies, and anatomy. Diploid and polyploid plants especially have different morphology, physiology, cellularity, and biochemistry. As a result, polyploidy has been identified as an essential component in determining plant salt tolerance. To evaluate the effects of salt (NaCl) stress on sugar beet genotypes, diploid (2X), triploid (3X), and tetraploid (4X) genotypes were exposed to 0 (control), 50, and 150 mM NaCl concentrations for seven weeks. Under control conditions, the diploid (2X) genotype showed higher growth performance compared to the tetraploid (4X) and triploid (3X) genotypes, respectively. Regarding germination and early-stage growth performance, a reduction of about 50% was observed in the diploid (2X) genotype under salt stress compared to the control condition. The diploid (2X) genotype showed higher germination, a greater salt tolerance index, and better seedling growth performance than the other ploidy levels. Late-stage growth, leaf length, leaf width, leaf area, cytological findings, and total chlorophyll content were all shown to be higher and less reduced (around 30%) under salt stress in diploid (2X) genotypes. Even though all of the findings in this study showed a decrease when plants were exposed to salt (NaCl), the diploid (2X) ploidy level plants displayed more robust growth and development than the triploid (3X) and tetraploid (4X) genotypes.